2021
DOI: 10.1007/s11060-021-03895-4
|View full text |Cite
|
Sign up to set email alerts
|

Reforming support systems of newly diagnosed brain cancer patients: a systematic review

Abstract: Purpose Despite the increasing incidence of currently incurable brain cancer, limited resources are placed in patients’ support systems, with reactive utilisation late in the disease course, when physical and psychological symptoms have peaked. Based on patient-derived data and emphasis on service improvement, this review investigated the structure and efficacy of the support methods of newly diagnosed brain cancer patients in healthcare systems. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(189 reference statements)
1
6
0
Order By: Relevance
“…also highlighted the importance of communicating with carers to improve end of life care and reduce carer distress burnout and bereavement. Targeted communication skills training for clinicians focusing on communicating and assessing distress and unmet needs for people diagnosed with a brain tumour and their carers may assist clinicians in providing support and referring appropriately 38 . It is imperative cancer services, primary health care networks, and non‐government organisations such as Cancer Councils, work together to fill the gaps in care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also highlighted the importance of communicating with carers to improve end of life care and reduce carer distress burnout and bereavement. Targeted communication skills training for clinicians focusing on communicating and assessing distress and unmet needs for people diagnosed with a brain tumour and their carers may assist clinicians in providing support and referring appropriately 38 . It is imperative cancer services, primary health care networks, and non‐government organisations such as Cancer Councils, work together to fill the gaps in care.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted communication skills training for clinicians focusing on communicating and assessing distress and unmet needs for people diagnosed with a brain tumour and their carers may assist clinicians in providing support and referring appropriately. 38 It is imperative cancer services, primary health care networks, and non‐government organisations such as Cancer Councils, work together to fill the gaps in care. Further research is warranted to trial interventions to reduce patient and carer distress and address brain cancer specific unmet needs.…”
Section: Discussionmentioning
confidence: 99%
“…2,9 A recent systematic review found that care coordination and continuity, personalized information, and effective communication increased individuals' sense of support at diagnosis, irrespective of discipline. 30 Little is known, however, about the scope of practice of professionals involved in psychological support and whether this differs according to discipline and illness phase.…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary approaches to psychological support are strongly advocated, with recognition that medical, nursing, and allied health professionals can have differing yet complementary roles in provision of supportive care 2,9 . A recent systematic review found that care coordination and continuity, personalized information, and effective communication increased individuals' sense of support at diagnosis, irrespective of discipline 30 . Little is known, however, about the scope of practice of professionals involved in psychological support and whether this differs according to discipline and illness phase.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, many studies use quantitative methods to assess QoL in cancer patients [65][66][67][68][69]. Yet, at the same time, there is a lack of observations concerning the specific configuration of the patient's condition, including how the patient describes such a condition, how he/she gives a self-description and how he/she describes the other significant roles, and how the patient considers their own illness and symptoms.…”
Section: Discussionmentioning
confidence: 99%